2008
DOI: 10.1038/sc.2008.116
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation outcomes in people with pre-morbid mental health disorders following spinal cord injury

Abstract: All patients were involved in a multidisciplinary Goal Planning and Needs Assessment Rehabilitation Programme. Rehabilitation outcomes were measured using the Needs Assessment Checklist (NAC), which has been specifically designed for use with people with SCI. It is a reliable and valid clinical assessment tool, which provides a means to assess and facilitate the delivery of an individually tailored rehabilitation programme. Results: No significant difference was found between the MHD and non-MHD groups for reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…Overall, there was no significant difference for the discharge SCIM between the cases and controls, which answers our second question-do people with MHD have poorer outcomes from SCI rehabilitation than those without MHD? This supports the research by Kennedy et al 5 in 2009 who demonstrated improving scores of the Needs Assessment Checklist in patients with MHD.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Overall, there was no significant difference for the discharge SCIM between the cases and controls, which answers our second question-do people with MHD have poorer outcomes from SCI rehabilitation than those without MHD? This supports the research by Kennedy et al 5 in 2009 who demonstrated improving scores of the Needs Assessment Checklist in patients with MHD.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of pre-existing MHD among patients in this sample was substantially larger than previous research has indicated. 5 This may be related to the population coming from the London area, given previous evidence of a link between urbanicity and MHD rates and morbidity. 14,15 Alternatively, it may be in other settings, MHD is underrecognised or people with MHD are not being admitted for rehabilitation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This research enabled subsequent mapping to develop [41] and international audits [42] based on the findings. Outcome data from the NAC (now SMS-NAC) has also been used to evidence the impact of the programme, examining whether goal achievement varies for a range of potentially marginalised groups, including older adults [43] and people with pre-injury mental health needs [44], comparing outcome with respect to ethnicity [45], injury aetiology [46][47][48] and psychological need [49]. The breadth of the domains and items on the NAC (now SMS-NAC) has enabled self-management concerns such as skin knowledge skills development through rehabilitation to be examined [19,50,51] and issues such as pain [52] and return-towork intentions to be tracked [53], with recent reporting of the mediating relationship that appraisals provide for mood and self-management on the skin and bladder domains [54].…”
Section: Introductionmentioning
confidence: 99%